2017
DOI: 10.1016/j.scriptamat.2016.10.018
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-high temperature ceramics: Materials for extreme environments

Abstract: This paper identifies gaps in thepresent state of knowledge and describes emerging research directions for ultra-high temperature ceramics. Borides, carbides, and nitrides of early transition metals such as Zr, Hf, Nb, and Ta have the highest melting points of any known compounds, making them suitable for use in extreme environments.Studies of synthesis, processing, densification, thermal properties, mechanical behavior, and oxidation of ultra-high temperature ceramics have generated a substantial base of know… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
343
1
8

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 750 publications
(356 citation statements)
references
References 70 publications
4
343
1
8
Order By: Relevance
“…Belong to the family of UHTCs of Group IV metal carbides, borides and nitrides, Hafnium diboride (HfB 2 ) and Zirconium diboride (ZrB 2 ) have unique combinations of thermophysical properties, including high melting point, high modulus and hardness, high thermal conductivity and high resistance to chemical attack [1][2][3][4][5]. Compared to ZrB 2 , oxidation resistance of HfB 2 is better [1].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Belong to the family of UHTCs of Group IV metal carbides, borides and nitrides, Hafnium diboride (HfB 2 ) and Zirconium diboride (ZrB 2 ) have unique combinations of thermophysical properties, including high melting point, high modulus and hardness, high thermal conductivity and high resistance to chemical attack [1][2][3][4][5]. Compared to ZrB 2 , oxidation resistance of HfB 2 is better [1].…”
Section: Introductionmentioning
confidence: 99%
“…Compared to ZrB 2 , oxidation resistance of HfB 2 is better [1]. As a result, HfB 2 -based ceramics have been considered as promising candidates for ultra-high temperature applications, such as propulsion systems, rocket nozzles, sharp leading edges and nose cones.…”
Section: Introductionmentioning
confidence: 99%
“…They are ceramic materials with properties such as high hardness, high wear resistance, high melting points, chemical inertness, and often metallic conduction [1]. These properties make transition metal borides promising for several potential applications, for example as electrical contact materials in demanding environments, in aerospace applications and as hard protective coatings in metal cutting [2]. The most common crystal structure for the transition metal borides is the AlB2-type.…”
Section: Introductionmentioning
confidence: 99%
“…When grain coarsening occurs in UHTCs the mechanical properties are detrimentally effected compared with ceramics with refined microstructures [68]. By analyzing the instantaneous relative density during the SPS process it was observed that the sample reached its greatest density after about a minute and a half into hold time at 1850°C as seen in Figure 47.…”
Section: = ( )mentioning
confidence: 99%